The abundant world: Paul Feyerabend's metaphysics of science. (June 2016) - Brown, Matthew J.
Abstract: The goal of this paper is to provide an interpretation of Feyerabend's metaphysics of science as found in late works like Conquest of Abundance and Tyranny of Science . Feyerabend's late metaphysics consists of an attempt to criticize and provide a systematic alternative to traditional scientific realism, a package of views he sometimes referred to as "scientific materialism." Scientific materialism is objectionable not only on metaphysical grounds, nor because it provides a poor ground for understanding science, but because it implies problematic claims about the epistemic and cultural authority of science, claims incompatible with situating science properly in democratic societies. I show how Feyerabend's metaphysical view, which I call "the abundant world" or "abundant realism, " constitute a sophisticated and challenging form of ontological pluralism that makes interesting connections with contemporary philosophy of science and issues of the political and policy role of science in a democratic society. Highlights: Provides an interpretation of Feyerabend's metaphysics of science as found in late works like Conquest of Abundance . Feyerabend's late metaphysics consists of an attempt to criticize and replace traditional scientific realism aka materialism. I describe Feyerabend's alternative view, "the abundant world" or "abundant realism." Feyerabend ultimately seeks to use metaphysics to improve the fit between science and democratic society.